A Theory of Social Forces and Immigrant Second Language Acquisition - Don J. DeVoretz; Christiane Werner (Institute for the Study of Labor (IZA), 2000)
The preponderance of minimal second language acquisition by immigrants worldwide is striking. This paper proposes a theoretical model, which analyzes the underlying forces that contribute to this outcome of minimal secondary language acquisition by immigrants in such diverse immigrant-receiving countries as Canada, Germany, Israel and the United States. It is argued that the weak incentive structures for second language acquisition for an immigrant appear in four analytically separate spheres including the labour market, political, social, and education spheres. Furthermore, two integration regimes are imposed in these spheres – no government interference, or government-mandated minimum language acquisition after arrival. In all cases and in all spheres, it is argued that, for the majority of immigrants, the weakest level of second language acquisition – minimum oral and minimum written – is the optimal outcome given their incentive structure. In addition, the labour market is the primary determinant of this outcome. Finally, several policy measures to increase the incentives for further second language acquisition are explored.
Keywords: J61; J24; 330; Immigration; ethnic Germans; Canada; language acquisition; labour market; integration; assimilation; Migranten; Mehrsprachigkeit; Soziale Integration; Opportunitätskosten; Arbeitsmarkt; Theorie; Deutschland; Kanada